Factors Related to Personal Hygiene of Traditional Jamu Handler in Bantul District, Indonesia - Suryani, Dyah; Indriani, Atika Rahma; Suyitno, Suyitno (GHMJ (Global Health Management Journal), 2025)
Background: Foodborne disease is the contamination of pathogenic bacteria that multiply in drinks. Traditional jamu handlers, people who process conventional jamu, need to implement and understand the importance of personal hygiene to avoid bacterial contamination. Aims: This study aimed to determine the relationship between knowledge, attitude, sanitation facilities and infrastructure, participation in counseling, and level of education with personal hygiene in traditional jamu handlers in Kiringan Village, Bantul District, Yogyakarta Province, Indonesia. Methods: This study used a quantitative approach with a cross-sectional design, involving 73 traditional jamu handlers who were selected by simple random sampling from a population of 90 handlers. The dependent variable was the personal hygiene of jamu handlers, measured using an observation checklist and categorized as "appropriate" or "not appropriate" based on an average score of 7.12. Independent variables included knowledge, attitudes, sanitation facilities and infrastructure, participation in counseling, and education level, which were assessed using questionnaires and observation sheets. Statistical analysis included identification of respondent characteristics to describe the sample and bivariate analysis to evaluate the relationship between independent and dependent variables. Results: The finding of this study showed that the level of knowledge, attitude, availability of sanitation facilities, participation in food safety counseling, and education level had a significant relationship with personal hygiene practices in traditional jamu handlers. Higher education levels had the most significant impact on improving good hygiene practices. Conclusion: Personal hygiene of handlers was influenced by knowledge, attitudes, sanitation facilities and infrastructure, participation in food safety counseling, and level of education. It is suggested to increase awareness and implementation of personal hygiene when processing traditional jamu and routinely attend food safety counseling to increase knowledge. Received: 24 December 2024 | Reviewed: 28 December 2024 | Revised: 13 January 2025 | Accepted: 23 January 2025.